“Pemetaan Multidimensi Literasi Asesmen Guru Pendidikan Anak Usia Dini dan Hambatan dalam Implementasi Asesmen Otentik: Bukti dari Kota Semarang.” - Muniroh Munawar; Mila Karmila; Aurora Nur Aini (LPPM Universitas Pendidikan Mandalika, 2026)
This study aims to map the level of assessment literacy among early childhood education (ECE) teachers in Semarang City and to identify the challenges associated with implementing authentic assessment. The study employed a quantitative approach with a descriptive design. The sample consisted of 583 ECE teachers selected through proportionate random sampling. The instrument used was a Likert-scale questionnaire measuring five dimensions: assessment understanding, planning and implementation, recording and data processing, supporting and inhibiting factors, and professional development. The questionnaire was developed based on construct validity procedures and pilot-tested on 30 respondents. Of the initial 31 statement items, 23 were declared valid, with validity coefficients ranging from 0.392 to 0.691. The reliability test produced a Cronbach’s Alpha coefficient of 0.871, indicating high reliability. Data were analyzed using descriptive statistics, including percentages and frequency distributions. The findings indicate that teachers’ assessment literacy is at a moderate level, with stronger technical competence than conceptual and analytical competence. Teachers still experience difficulties in understanding fundamental assessment concepts, determining developmental indicators, and interpreting assessment results for instructional decision-making. In addition, major challenges arise from structural factors, such as limited time, inadequate facilities, insufficient institutional support, and unequal access to professional development opportunities. This study contributes by providing a multidimensional profile of assessment literacy encompassing conceptual, technical, analytical, structural, and professional aspects. The findings may serve as a foundation for the development of a contextual play-based assessment model.